Pathokinematics of precision pinch movement associated with carpal tunnel syndrome. Issue 6 (17th February 2014) - Nataraj, Raviraj; Evans, Peter J.; Seitz, William H.; Li, Zong‐Ming
ABSTRACT Carpal tunnel syndrome (CTS) can adversely affect fine motor control of the hand. Precision pinch between the thumb and index finger requires coordinated movements of these digits for reliable task performance. We examined the impairment upon precision pinch function affected by CTS during digit movement and digit contact. Eleven CTS subjects and 11 able‐bodied (ABL) controls donned markers for motion capture of the thumb and index finger during precision pinch movement (PPM). Subjects were instructed to repetitively execute the PPM task, and performance was assessed by range of movement, variability of the movement trajectory, and precision of digit contact. The CTS group demonstrated shorter path‐length of digit endpoints and greater variability in inter‐pad distance and most joint angles across the PPM movement. Subjects with CTS also showed lack of precision in contact points on the digit‐pads and relative orientation of the digits at contact. Carpal tunnel syndrome impairs the ability to perform precision pinch across the movement and at digit‐contact. The findings may serve to identify deficits in manual dexterity for functional evaluation of CTS. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:786–792, 2014.